How does the social media platform TikTok influence the intention to buy snacks: An empirical study of the Vietnamese youth generation. - Thi Huong Tran; The-Bao Luong; Mai Phuong Uyen Ho; Hoang Anh Le; Mai Kim Chi Le (Journal of Business & Management, 2023)
The study was conducted to identify the factors influencing the behaviour of buying street food through TikTok among the young generation in Ho Chi Minh City. Through surveying 459 consumers and filtering the appropriate survey samples for the study, 434 suitable samples were obtained: describing the variables of the scale, testing Cronbach's Alpha, and conducting regression analysis. The factors surveyed showed that five factors affect the behavior of buying snacks and other products through TikTok among the youth: perception of usefulness, credibility, interest, price expectations, and reference group. Therefore, the study also proposes solutions for food businesses on TikTok to attract customers better. At the same time, some solutions for TikTok users to use the application more efficiently are also suggested